Iodine-containing supplement use by pregnant women attending antenatal clinics in Western Australia - Hine, Tammy; Zhao, Yun; Begley, Andrea; Skeaff, S.; Sherriff, Jill (Wiley-Blackwell Publishing Asia, 2018)
BACKGROUND: Iodine requirements increase during pregnancy and although national recommendations for daily iodine supplementation (150 µg) exist, there is no research related to the uptake of these recommendations by pregnant women in Western Australia. AIMS: To investigate the use of iodine-containing supplements and associations with their use in a sample of Western Australian pregnant women. MATERIALS AND METHODS: A cross-sectional study was conducted on pregnant women attending antenatal clinics in a public tertiary hospital for women and neonates in Perth during 2012 and 2013 (n = 425). Women completed a self-administered questionnaire. Frequencies and percentages were obtained for categorical variables and ?2 tests conducted to assess associations between iodine-containing supplement use and sociodemographic and pregnancy-related factors. RESULTS: A total of 24% of pregnant women reported using iodine-containing supplements prior to pregnancy compared to 66% during the previous two months. Age and maternal income were associated with use prior to pregnancy only (P = 0.004 and P = 0.031) and first pregnancy was associated with use during pregnancy only (P = 0.006). Ethnicity and reporting use in the first two trimesters were associated with the use of iodine supplements both in the year prior to pregnancy (P = 0.002 and P = 0.020, respectively) and during pregnancy (P < 0.001 and P = 0.001, respectively). CONCLUSIONS: Two-thirds of women reported use of iodine-containing supplements during pregnancy, within the range reported for other Australian states. One-quarter reported use prior to pregnancy. Public health strategies are required to promote awareness of the importance of iodine and supplementation both before and during the entire pregnancy.